Metoda izbora odvodnika prenapona za unapređenje koordinacije izolacije u visokonaponskim sustavima : doktorski rad - Filipović-Grčić, Božidar; Uglešić, Ivo (Zagreb : B. Filipović-Grčić ; Fakultet elektrotehnike i računarstva, 2013)
Prikladan odabir nazivnog napona, energetske klase te mjesta ugradnje odvodnika prenapona rezultira učinkovitim ograničenjem prenapona, odnosno unapređenjem koordinacije izolacije u elektroenergetskom sustavu. U doktorskom radu analizirane su mogućnosti unapređenja koordinacije izolacije u visokonaponskim sustavima novom metodom izbora odvodnika prenapona. Metoda je s obzirom na vrstu prenapona raščlanjena na tri međusobno povezana dijela. Prvi dio metode odnosi se na izbor odvodnika s minimalnim nazivnim naponom i energetskom klasom koji se neće energetski preopteretiti uslijed privremenih prenapona. U tu svrhu razvijen je računski model odvodnika, koji je eksperimentalno verificiran, za proračun energetskog opterećenja uslijed privremenih prenapona. Metoda je verificirana na primjeru unapređenja prenaponske zaštite kompaktiranog dalekovoda u djelomično uzemljenoj 400 kV mreži. Prema rezultatima proračuna, moguće je izabrati odvodnik s boljim zaštitnim karakteristikama (nižim preostalim naponom), u odnosu na izbor prema normi IEC 60099-5. Drugi dio metode odnosi se na izbor energetske klase i mjesta ugradnje odvodnika s obzirom na sklopne prenapone. Razmatrana je mogućnost kompaktiranja 400 kV dalekovoda smanjenjem faznih i međufaznih razmaka. Izrađen je algoritam kojim se procjenjuje rizik pojave preskoka. Rezultati pokazuju kako je moguće znatno smanjiti izolacijske razmake na dalekovodu uz prihvatljiv rizik pojave preskoka. Treći dio metode obuhvaća izbor energetske klase odvodnika i unapređenje koordinacije izolacije rasklopnih postrojenja s obzirom na atmosferske prenapone. Detaljno su istraženi parametri koji utječu na energetsko opterećenje odvodnika na dalekovodima. Metoda je verificirana na primjeru 110 kV i 220 kV rasklopnog postrojenja. - KLJUČNE RIJEČI: odvodnik prenapona, metoda izbora, energetsko opterećenje, prenaponi, koordinacija izolacije, modeliranje, numerički proračuni, visokonaponski sustavi.
Insulation systems of HV equipment are continuously exposed to operating voltage and occasional overvoltages which cause the dielectric stresses of the insulation. Insulation should be dimensioned to withstand stresses during both the dielectric tests and in operation. Metal-oxide surge arresters are commonly installed in high voltage substations in the vicinity of the power transformers and in the transmission line bays for the limitation of lightning and switching overvoltages. The existing international standard IEC 60099-5 defines a pretty rough procedure for the selection of surge arrester parameters, i.e. rated voltage and energy class. Therefore in practice the surge arresters often have unjustifiably too high rated voltage and energy class. In order to effectively limit the overvoltages and to improve the insulation coordination in electric power system it is necessary to select the appropriate parameters of surge arresters, i.e. nominal voltage and energy class and to determine the optimal location of their installation. In the doctoral thesis the possibilities of improving the insulation coordination in high voltage systems were analysed using a new method for surge arresters selection. Doctoral thesis consists of eight chapters. In the introduction part, the importance of an effective overvoltage limitation and improvement of insulation coordination in electric power system is emphasized. Therefore, it is necessary to select the appropriate surge arresters parameters and to determine the optimal locations of their installation. A brief review of recent literature related to this problem is given. The main research objectives are given and a new integrated method of surge arresters selection for improvement of insulation coordination in high voltage systems is presented. The method consists of three interconnected parts considering the type of overvoltage. The method was verified on various examples that represent the worse cases regarding the overvoltage type. The second chapter gives an overview on insulation coordination and describes the characteristics of the surge arresters and the overvoltage protection in the electric power system. In the third chapter, a critical overview of standards and literature relating to the surge arrester energy stress is given. It was pointed out that the existing international standard IEC 60099-5 defines a pretty rough procedure for the selection of surge arrester parameters. In the fourth chapter, a computational model of surge arrester for calculation of energy stress due to temporary overvoltages was developed and experimentally verified by comparing the laboratory measurements and calculations. The fifth chapter presents the first part of the method referring to the selection of surge arrester with minimum rated voltage and energy class due to temporary overvoltages. The method was verified in case of improving the overvoltage protection of 400 kV compact transmission line in partially grounded network, with significant temporary overvoltages. A model for calculation of temporary overvoltages and load flow was developed. Calculations of combined temporary overvoltages caused by short circuit, Ferranti effect and load rejection were performed in order to determine the minimum rated voltage and energy stresses of surge arresters. The impact of relay protection system failure or delay on the surge arrester energy stress was analysed in the calculations. According to the results it is possible to select surge arrester with better protective characteristics (lower residual voltage) regarding to the selection according to IEC 60099-5. The sixth chapter presents the second part of the method referring to the selection of surge arrester energy class and optimum installation locations due to switching overvoltages. The method was verified in case of improving the overvoltage protection of compact transmission line uprated from 220 kV to 400 kV. The possibility of compacting 400 kV transmission line by reducing phase-to-earth and phase-to-phase air clearances was considered. Since there is a high risk of flashover due to the reduced insulation clearances, an algorithm which estimates the risk of flashover due to switching overvoltages was developed. According to the calculation results it is possible to significantly reduce the insulation clearances on 400 kV transmission line, 350 km long, with an acceptable level of risk of flashover. By installing the surge arresters at five optimum locations on the transmission line the maximum phase-to-earth switching overvoltages decreased by 236 kV and the maximum phase-to-phase switching overvoltages decreased by 212 kV. Statistical switching withstand voltage of the transmission line insulators decreased by 274 kV with an acceptable risk of flashover. With the installation of additional transmission line surge arresters the energy stresses of substation surge arresters reduced and thus the lower energy class can be selected. In the seventh chapter, the third part of the method is presented referring to the selection of surge arrester energy class and improvement of insulation coordination in high voltage substations due to lightning overvoltages. The parameters affecting the energy stress of transmission line surge arresters due to lightning overvoltages were investigated in detail. The method was verified in case of 110 kV and 220 kV substations. Detailed model of substations and connected transmission lines was developed for calculation of lightning overvoltages. Calculation results show that with the installation of the transmission line surge arresters in the vicinity of substation the overvoltages on substation equipment decreased by 50 %. Therefore the overvoltage protection and insulation coordination are significantly improved. Energy stresses of surge arresters in substation decreased and the lower energy class can be selected. The eighth chapter refers to the concluding remarks and suggestions for the future research. By applying the proposed method the effective overvoltage protection is achieved with the surge arresters of lower energy class. This is economically justified since the price of surge arrester increases with the increase of energy class. - KEYWORDS: surge arrester, method of selection, energy stress, overvoltages, insulation coordination, modelling, numerical calculations, high voltage systems.
Bibliografija: str. 152-159. - Kazalo oznaka i kratica: str. 160-168